2011
DOI: 10.1007/s00404-011-2122-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance of peripheral (serum and molecular) blood markers for diagnosis of endometriosis

Abstract: A combination of serum and molecular markers could allow a better diagnosis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…CA125 is a valuable marker in the diagnosis of endometriosis. Previous studies showed significantly higher levels of CA125 in the serum of patients with endometriosis (9, 10). Our results also revealed that the serum level of CA125 was significantly increased in patients with endometriosis.…”
Section: Discussionmentioning
confidence: 82%
“…CA125 is a valuable marker in the diagnosis of endometriosis. Previous studies showed significantly higher levels of CA125 in the serum of patients with endometriosis (9, 10). Our results also revealed that the serum level of CA125 was significantly increased in patients with endometriosis.…”
Section: Discussionmentioning
confidence: 82%
“…In spite of affecting 5 to 10% of women in reproductive age, the exact etiology of the disease remains an intriguing enigma, since it is currently accepted that multiple factors are involved in the pathogenesis of endometriosis [2][3][4][5][6][7][8]. In addition to an invasive phenotype of endometrial cells, neoangiogenesis and sustained local inflammatory response are believed to be crucial points in the pathophysiology of endometriosis [9][10][11][12][13][14][15]. Neoangiogenesis is evident by the visualization of peripheral vascularization of ectopic endometriotic tissue at laparoscopy and increased angiogenic activity and vascular endothelial growth factor (VEGF) levels found in peritoneal fluid of patients with endometriosis [3,11,12,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Literature data show that combined multiple tumor markers, such as serum Ca 125, Ca 19.9 and mRNA for Survivin gene, can improve the overall diagnostic accuracy of all stages of primary ovarian epithelial tumors and allow a better triage between endometriosis and malignant adnexal masses [7,24,25]. Up until now, different risk models and screening algorithms that combine and evaluate tumor markers together, aimed at improving the specificity and sensitivity of diagnostic tests, and allowing for an effective triage of women to appropriate institutions for their care, have been developed so far.…”
Section: Discussionmentioning
confidence: 99%